The Influence of Return on Equity, Company Size, Price Earning Ratio, and Capital Structure on a Company’s Value - Alam Adhi Nugroho; Asep Muslihat (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2021)
For companies that have been gone public, the company’s value is a description of the market price of the company’s capital. Several factors can influence the company’s value, including return on equity, company size, price earning ratio, and capital structure. This study aims to determine and analyze the influence of return on equity, company size, price earning ratio, and capital structure on the company’s value in the automotive sub-sector companies and components listed on the IDX for the 2015-2019 period, either partially or simultaneously. The company’s value in this study was measured using Tobin’s Q. The sampling technique used in this study was purposive sampling. The number of samples is six from 13 companies. The data used are secondary data using the multiple linear regression analysis methods. This study indicates that the t-test shows that only partially return on equity affects the company’s value. In contrast, company size, price earning ratio, and capital structure do not affect the company’s value. Then the f-test shows that all independent variables simultaneously influence the company’s value.